Modeling the Main Determinants of Movie Sales: An Econometric Study of Chinese Marketplace - Feng, Fan; Sharma, Ravi (Journal of Reviews on Global Economics, 2016)
This paper investigates the financial performance of movies in China, a fast-growing commercial exhibition marketplace. Movie sales and Chinese market returns, movie characteristics and cultural contexts are operationalized in ordinary least squares (OLS) regression and quantile regression models to explain the highly varied acceptance across different products released since 2009. The samples comprise most of the widely released motion pictures in China. We posit that production budgets, sequels, audience ratings, cultural contexts and movie genres can significantly account for the variation in box office (BO) revenue and sales-revenue-to-cost (SRTC) within the Chinese market. Movies produced in countries with similar cultural contexts capture more audiences measured by box office proceeds, but it is noteworthy that SRTC falls at a decreasing rate as cultural differences increase. An increase in production budget generates more sales in China, but reduces the SRTC ratios with other factors controlled. Although aggregate cinema attendance may fluctuate with releasing date, this is not always true for an individual movie's financial success. Quantile regressions provide us with a richer characterization of the relationship, enabling us to analyze the entire distribution of box office proceeds and SRTC ratios, as well as their determinants at key quantiles.